1979
DOI: 10.1042/bj1820455
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of mitochondrial calcium ion efflux by thiol-specific reagents and by thyroxine. The relationship to adenosine diphosphate retention and to mitochondrial permeability

Abstract: Respiring rat heart mitochondria were loaded with Ca2+ and then treated with Ruthenium Red. The factors affecting the subsequent Ca2+ efflux were studied. Addition ofrotenone or antimycin led to a decline of efflux except at pH values above 7.2, provided the load was less than about 80nmol per mg of protein. Oligomycin reversed the effect of the respiratory inhibitors. Independently of respiration, efflux was stimulated by the uncoupler trifluoromethyltetrachlorbenzimadazole, by mersalyl and by thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(24 citation statements)
references
References 42 publications
1
21
2
Order By: Relevance
“…Since isolated mitochondria can rapidly take up large quantities of calcium from the suspension medium (reviewed by Lehninger, Carafoli & Rossi, 1967), the question of the cellular mechanisms which control 0022-2631/81/0062-0053 $02.20 9 1981 Springer-Verlag New York Inc. the release of this accumulated calcium has also concerned many investigators (reviewed by Bygrave, 1978;Nicholls & Brand, 1980;and Lehninger, Vercesi & Bababunmi, 1978;Harris, A1-Shaikhaly & Baum, 1979;L6tscher, Winterhalter, Carafoli & Richter, 1979;Roman, Gmaj, Nowicka &Angielski, 1979;Haworth, Hunter & Berkoff, 1980;Juzu & Holdsworth, 1980). However, most experiments designed to investigate this question have tested the ability of a given agent to induce a release of calcium from isolated mitochondria which have previously been permitted to accumulate relatively large amounts (greater than 20 nmol/mg protein) of the cation (Borle, 1974;Peng, Price, Bhuvaneswaran & Wadkins, 1974;Binet & Volfin, 1975;Schotland & Mela, 1977 ;Lehninger et al, 1978 ;Harris et al, 1979;L6tscher et al, 1979;Roman et al, 1979).…”
mentioning
confidence: 99%
“…Since isolated mitochondria can rapidly take up large quantities of calcium from the suspension medium (reviewed by Lehninger, Carafoli & Rossi, 1967), the question of the cellular mechanisms which control 0022-2631/81/0062-0053 $02.20 9 1981 Springer-Verlag New York Inc. the release of this accumulated calcium has also concerned many investigators (reviewed by Bygrave, 1978;Nicholls & Brand, 1980;and Lehninger, Vercesi & Bababunmi, 1978;Harris, A1-Shaikhaly & Baum, 1979;L6tscher, Winterhalter, Carafoli & Richter, 1979;Roman, Gmaj, Nowicka &Angielski, 1979;Haworth, Hunter & Berkoff, 1980;Juzu & Holdsworth, 1980). However, most experiments designed to investigate this question have tested the ability of a given agent to induce a release of calcium from isolated mitochondria which have previously been permitted to accumulate relatively large amounts (greater than 20 nmol/mg protein) of the cation (Borle, 1974;Peng, Price, Bhuvaneswaran & Wadkins, 1974;Binet & Volfin, 1975;Schotland & Mela, 1977 ;Lehninger et al, 1978 ;Harris et al, 1979;L6tscher et al, 1979;Roman et al, 1979).…”
mentioning
confidence: 99%
“…Examples are mercurials [18,19], a quinone [19], diamide [5,25] and t-butyl hydroperoxide [24,26]. In the latter context, there is evidence [24] that it is only when glutathione peroxidase is active, so that GSH was consumed, that there is an induction of Ca 2+ release by the peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria were prepared from rat liver [17] and rat heart [18]. The superoxide generating system used was a mixture of xanthine (0.5 mM) and xanthine oxidase (22 or 44 mU).…”
Section: Methodsmentioning
confidence: 99%
“…Rat heart mitochondria were prepared by a modification of the previous procedure (Harris & Zaba, 1977;Harris et al, 1979), which was introduced after a suggestion made by Vercesi et al (1978). The minced tissue obtained from the Climpex mincer was digested with 1 mg each of trypsin and collagenase per g of tissue in 5 ml of medium at 00C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…This set of observations led to the proposal that thiol groups were involved in keeping ADP and Mg2+ ions bound to the membrane, in which condition permeability was low. The finding that low Ca2+ efflux is favoured by a reduced state of the nicotinamide nucleotides obtained alternatively by favourable substrate or by respiratory inhibition (Harris, 1979b;Harris et al, 1979) suggested that there is a passage of reducing equivalents from NADH to generate NADPH and so feed substrate to glutathione reductase to provide a source of new thiol groups. Respiratory inhibition is effective in this regard only if there is endogenous Vol.…”
mentioning
confidence: 99%